Efficient synthesis of ethyl 2-(oxazolin-2-yl)alkanoates via ethoxycarbonylketene-induced electrophilic ring expansion of aziridines - Lei, Yelong; Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2022)
Alkyl 2-diazo-3-oxoalkanoates generate alkoxycarbonylketenes, which undergo an electrophilic ring expansion with aziridines to afford alkyl 2-(oxazolin-2-yl)alkanoates in good to excellent yields under microwave heating. The method is a convenient and clean reaction without any activators and catalysts and can be also applied in the synthesis of 2-(oxazolin-2-yl)alkanamides and 1-(oxazolin-2-yl)alkylphosphonates.
Keywords: aziridine; diazooxoester; diazo compound; ketene; oxazoline; ring expansion